Numerical analysis of a double shear standard bolted connection considering monotonic loadings. Issue 4 (2nd October 2017) - Rodrigues, Mariana Ferreira; Correia, José; Pedrosa, Bruno; de Jesus, Abílio; Carvalho, Bruno; Rebelo, Carlos; Xavier, José; Calçada, Rui
Abstract: The behaviour of standard bolted steel connections submitted to monotonic loads, through the use of numerical models, is presented in the current paper. The bolted connections allow speed up constructive processes in an increasingly competitive and globalized world in which the costs are a decisive factor in the development of a project. The use of computational tools in the analysis of bolted connections becomes determinant, mainly for new solutions or solutions less explored in terms of design codes. Throughout the years, bolted connections have been suffering transformations resulting from research activities performed by many authors. Rivets have been replaced by bolts, the main achievement being the pre-stressed bolts. Methodologies based on finite element analyses were proposed for double shear bolted connection. The non-linear behaviour of these connections is investigated and their performances are compared. In the numerical modelling of the bolted connection, linear elastic and elastoplastic analyzes reveal that there are two slip levels associated with local non-linearities caused by the contact pairs, which vary with clamping stresses.